#TITLE_ALTERNATIVE# - AMRAN (NIM 12104071); Pembimbing : Prof. Dr. Ir. Arief Sudarsono, M.Sc., YUSRINA
Separation of alumina and red mud from bauxite using the Bayer process was found by Karl Bayer in 1888. This process produces bauxite residue known as red sludge (red mud) that contains oxides of iron, silicon, titanium and other minor impurities. The processing of red mud is one of mining activity aspect generating significance environmental impact. That is why the study of the processing of bauxite red mud needs to be developed furthermore, so red mud can be properly exploited. This research is intended as a preliminary study to extract mineral iron concentrate from red mud bauxite and to increase its grade by way of scale classification using Krebs Hidrocyclone with 1 inch of diameter. Through separation mechanism by using hidrocyclone, the coarse particles containing iron mineral will flow down as underflow meanwhile fine materials as overflow. Parameters used in this final assignment research are combined solid and pressure percentage in order to achieve optimum variation to separate iron concentrate from red mud using Krebs Hidrocyclone with 1 inch of diameter. The concentrate acquired from this testing is then chemically analyzed to determine its grade and furthermore to calculate the iron mineral recovered from the process. Data acquired from this analysis is then flowed into each variable's graph to observe the variable's effect on the level of concentration and recovery. Result from the test using hidrocyclone shown that the highest concentration (grade) of Fe2O3 was achieved at 44.3% of 5% solid and 1 bar of pressure. The highest recovery was achieved at level 44.14% of 5% solid and 4 bar of pressure with particle size Ã‚Â–35 mesh. Furthermore, mineralogy analysis is done to observe the rate of change in mineral composition in the concentrate which give the highest and the lowest level of iron in the red mud.